2020
DOI: 10.1167/tvst.9.10.9
|View full text |Cite
|
Sign up to set email alerts
|

Edge of Scotoma Sensitivity as a Microperimetry Clinical Trial End Point in USH2A Retinopathy

Abstract: Purpose Microperimetry is commonly used to assess retinal function. We perform cross-sectional and longitudinal analysis on microperimetry parameters in USH2A retinopathy and explore end points suitable for future clinical trials. Methods Microperimetry was performed using two grids, Grid 1 (18° diameter) and Grid 2 (6° diameter). In Grid 1, four parameters (number of nonscotomatous loci, mean sensitivity [MS], responding point sensitivity [RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Charng and colleagues recently analyzed MAIA MP cross-sectionally and longitudinally in a cohort of 16 patients with USH2A-related retinal degeneration. 46 Using a grid with a diameter of 18°, they noted a mean sensitivity of 10.0 dB. The higher mean sensitivity value than that shown in our study was expected given the smaller grid used in that trial compared to the 30°diameter pattern employed in the RUSH2A study.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Charng and colleagues recently analyzed MAIA MP cross-sectionally and longitudinally in a cohort of 16 patients with USH2A-related retinal degeneration. 46 Using a grid with a diameter of 18°, they noted a mean sensitivity of 10.0 dB. The higher mean sensitivity value than that shown in our study was expected given the smaller grid used in that trial compared to the 30°diameter pattern employed in the RUSH2A study.…”
Section: Discussionsupporting
confidence: 45%
“…The higher mean sensitivity value than that shown in our study was expected given the smaller grid used in that trial compared to the 30°diameter pattern employed in the RUSH2A study. The authors also demonstrated that sensitivity at the edge of the scotoma had the fastest rate of functional decline over an average of 2.6 years compared to mean sensitivity and responding point sensitivity, 46 suggesting that the edge of scotoma sensitivity would be a useful metric for longitudinal analysis in the RUSH2A study.…”
Section: Discussionmentioning
confidence: 96%
“…VENTURE is a rapidly expanding database that will be actively utilised to support future IRD research and the development of IRD treatments in Australia. The VENTURE study team aims to collaborate closely with clinicians, support organisations, and other research groups across Australia and New Zealand, 16,38,44,47 to maximise the outreach and potential benefit to the IRD community. This protocol intends to promote collaboration, open communications and the sharing of expertise and knowledge amongst IRD research groups in this region.…”
Section: Discussionmentioning
confidence: 99%
“…79 Furthermore, analyses of the results from microperimetry testing with standardized stimulus patterns could also be limited post hoc to at-risk locations, such as those in the junctional zone external to atrophic regions in eyes with GA 10,11 and Stargardt disease, 12,13 or those internal to the boundary of atrophic region in retinitis pigmentosa. 14…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Furthermore, analyses of the results from microperimetry testing with standardized stimulus patterns could also be limited post hoc to at-risk locations, such as those in the junctional zone external to atrophic regions in eyes with GA 10,11 and Stargardt disease, 12,13 or those internal to the boundary of atrophic region in retinitis pigmentosa. 14 To accurately interpret microperimetry (or any type of perimetry) data, it is critical to determine the sensitivity loss from the expected age-and location-specific normal sensitivity. 15 In addition, there are specific regions of the visual field where the interindividual variation in visual sensitivity may be lower or higher.…”
Section: Introductionmentioning
confidence: 99%